Epicardial and Intramyocardial Adipose Tissue: The Enemy within - Baker, A. R.; Creely, S. J.; McTernan, P. G.; Kumar, S. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2007)
Both obesity and lipodystrophy are associated with an accumulation of lipid in tissues other than the classical adipose tissue depots. The consequences of this ectopic fat are not limited to the now well established insulin resistance but also a range of other organ specific sequelae. We discuss, with specific reference to the heart, the potential role of ectopic adipocyte proliferation as well as intracellular lipid accumulation. This is a relatively recently described phenomenon, but has attracted the attention of scientists because of the association with visceral obesity. A range of therapeutic agents have been shown to be effective in targeting ectopic fat with much evidence supporting the role of peroxisome proliferator- activated receptor-gamma agonists. Other novel approaches are emerging from the raft of studies into both human and rodent adipobiology, but it is too early to say if intervention brings any clinical benefits.
Keywords: fatty heart